Soft Tissue Release for Neglected Clubfoot: One-year Clinical Outcome - Husnul Fuad Albar (Cermin Dunia Kedokteran, 2022)
Background. Neglected clubfoot is the most common congenital problem leading to locomotor disability. Eighty percent children with clubfoot deformity are born in developing world and the majority do not have access to appropriate medical care. The severity of clubfoot may be assessed with a variety of methods; i.e Pirani scoring system. This study use Pirani scoring system to evaluate the clinical outcome of neglected clubfoot patients one year after soft tissue release. Method. A study of 17 patients who underwent soft tissue release in Harapan Hospital a year before. We compare Pirani score before and one year after soft tissue release. Other data submitted are age, reason of delayed treatment, term of prosthesis, and complication after surgery. Result. The 17 patients were 10 females and 7 males; the average age was 69.06 ± 49.15 months old. Deformity in left foot was in 13 feet (59.1%) and right foot was in 9 feet (40.9%). The average total Pirani Score before soft tissue release is 5.43 ± 1.03 and one year after soft tissue release is 0.30 ± 0.40, p<0.0001 (p<0.05). This result shows significant improvement one year after soft tissue release. Conclusion. Soft tissue release for neglected clubfoot resulted in significant Pirani score improvement after one year. Latar Belakang. Neglected clubfoot merupakan masalah kongenital yang paling sering menyebabkan disabilitas lokomotor. Tingkat keparahan clubfoot dapat ditentukan dengan beberapa metode, antara lain sistem skor Pirani. Salah satu tata laksana neglected clubfoot adalah soft tissue release. Studi ini mengevaluasi keluaran klinis pasien neglected clubfoot menggunakan sistem skor Pirani satu tahun setelah soft tissue release. Metode. Studi pada 17 pasien yang telah menjalani soft tissue release satu tahun yang lalu. Skor Pirani sebelum dan satu tahun setelah soft tissue release dibandingkan. Data lain meliputi usia, alasan terlambatnya tata laksana, prosthesis yang digunakan, serta komplikasi pasca-operasi. Hasil. Rata-rata pasien berusia 69,06 ± 49,15 bulan, 10 perempuan dan 7 laki-laki. Sejumlah 13 deformitas didapatkan pada kaki kiri (59,1%), 9 deformitas pada kaki kanan (40,9%). Rata-rata skor Pirani sebelum soft tissue release adalah 5,43 ± 1,03, sedangkan rata-rata skor Pirani satu tahun setelah soft tissue release adalah 0,30 ± 0,40. Hasil ini menggambarkan peningkatan signifikan skor Pirani (p < 0,0001). Simpulan. Keluaran klinis pasien neglected clubfoot dinilai menggunakan skor Pirani meningkat signifikan satu tahun setelah soft tissue release.